2020
DOI: 10.1128/jvi.01788-20
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection and Persistence in Pulmonary Mucosal Double Negative T Cells In Vivo

Abstract: The lungs are relatively unexplored anatomical HIV reservoirs in the antiretroviral therapy (ART) era. Double negative (DN) T-cells are a subset of T-cells which lack expression of CD4 and CD8 (CD4-CD8-) and may play both regulatory and effector functions during HIV infection. Notably, circulating DN T-cells were previously described as cellular HIV reservoirs. Here, we undertook a thorough analysis of pulmonary versus blood DN T-cells of people living with HIV (PLWH) under ART. Bronchoalveolar lavage (BAL) fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Moreover, the lungs were enriched in activated memory CD4+ T-cells subsets that can further promote HIV replication and persistence (173). We also observed that pulmonary mucosal DN T cells of PLWH on ART expressed higher levels of HLA-DR and several cellular markers associated with HIV persistence (CCR6, CXCR3, and PD-1) compared to the blood (58). Importantly, CD3+CD4-CD8-DN T-cells from the BAL fluid of these participants harbored HIV DNA.…”
Section: Hiv Persists In Multiple Lung Immune Cell Typesmentioning
confidence: 56%
See 4 more Smart Citations
“…Moreover, the lungs were enriched in activated memory CD4+ T-cells subsets that can further promote HIV replication and persistence (173). We also observed that pulmonary mucosal DN T cells of PLWH on ART expressed higher levels of HLA-DR and several cellular markers associated with HIV persistence (CCR6, CXCR3, and PD-1) compared to the blood (58). Importantly, CD3+CD4-CD8-DN T-cells from the BAL fluid of these participants harbored HIV DNA.…”
Section: Hiv Persists In Multiple Lung Immune Cell Typesmentioning
confidence: 56%
“…Importantly, CD3+CD4-CD8- DN T-cells from the BAL fluid of these participants harbored HIV DNA. Using the humanized bone marrow-liver-thymus mouse model, our group also observed higher infection frequencies of lung DN T-cells than those of the blood and spleen in both early and late HIV infection stages, meaning that apart from AMs and CD4 T-cells, HIV is also seeded in pulmonary mucosal DN T-cells early following infection and persists in these potential cellular HIV reservoirs even during long-term ART ( 58 ).…”
Section: Lungs As An Hiv Reservoirmentioning
confidence: 92%
See 3 more Smart Citations